2013
DOI: 10.1038/mt.2013.196
|View full text |Cite
|
Sign up to set email alerts
|

Inactive ERBB Receptors Cooperate With Reactive Oxygen Species To Suppress Cancer Progression

Abstract: The ERBB receptors are a family of heterodimerization partners capable of driving transformation and metastasis. While the therapeutic targeting of single receptors has proven efficacious, optimal targeting of this receptor family should target all oncogenic members simultaneously. The juxtamembrane domains of ERBB1, ERBB2, and ERBB3 are highly conserved and control various aspects of ERBB-dependent biology. In an effort to block those functions, we have targeted this domain with decoy peptides synthesized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…However,w en oted that these developmental and metabolism networks are involved in the regulation of reactive oxygen species (ROS) formation. [32] In addition, the fingerprint determined for PFP 14 dk at 30 mm showed 88 %s imilarity to the fingerprint determined for aumitin (19,F igure 3a), ak nown inhibitor of mitochondrial respiration by targeting mitochondrial complex I. [31d] Since these results suggested that pseudo NP 14 dk may modulate mitochondrial function as well, aM ito Stress Test assay was carried out employing the Seahorse XF analyzer as previously reported.…”
Section: Angewandte Chemiementioning
confidence: 71%
“…However,w en oted that these developmental and metabolism networks are involved in the regulation of reactive oxygen species (ROS) formation. [32] In addition, the fingerprint determined for PFP 14 dk at 30 mm showed 88 %s imilarity to the fingerprint determined for aumitin (19,F igure 3a), ak nown inhibitor of mitochondrial respiration by targeting mitochondrial complex I. [31d] Since these results suggested that pseudo NP 14 dk may modulate mitochondrial function as well, aM ito Stress Test assay was carried out employing the Seahorse XF analyzer as previously reported.…”
Section: Angewandte Chemiementioning
confidence: 71%
“…Overexpression of CaMKII resulted in inhibition of procaspase-7 and procaspase-8 expression. And the activation of caspase-2, -7, and -8 could be prevented or diminished by overexpression of CaMKII [ 40 ]. Cohen et al[ 41 ] reported that downregulation of ErbB could suppress the CaMKII signaling, which is coincident with the induction of apoptosis in breast and prostate cancer cells.…”
Section: The Role Of Camkii In Cancer Progressionmentioning
confidence: 99%
“…Targeted fused polypeptides are an emerging hotspot in targeted therapy for breast cancer. 23 , 24 There are a number of studies on the anticancer effect of targeted fused polypeptides in the treatment of breast cancer, including targeting the con-served transmembrane domain of human epidermal growth factor receptors, 25 29 glucose-regulated protein 78, 30 transferrin receptor, 31 and p53. 32 These targeted fused polypeptides exhibited a potent cell death inducing effect on tumor cells and a considerable suppressing effect on tumor growth and metastasis, indicating that the targeted fused polypeptide represents a promising targeted therapy strategy.…”
Section: Discussionmentioning
confidence: 99%